Simulation of dynamic load effect on power system frequency - Azizan, Abdul Rahman (2013)
This thesis addresses the impact of dynamic load on power system frequency. Rapid dynamic load variations will bring significant impact to the power system in terms of frequency. The thesis is based on three-phase dynamic load (composite based). The objective of this thesis was to analyse the dynamic characteristics of loads and its impact on power system frequency. For this, IEEE 9 bus system was tested with dynamic loads by observing change in power system frequency